Prefrontal activity predicts monkeys' decisions during an auditory category task - Lee, Jung Hoon; Russ, Brian E.; Orr, Lauren E.; Cohen, Yale (Frontiers in Integrative Neuroscience, 2009)
The neural correlates that relate auditory categorization to aspects of goal-directed behavior, such as decision-making, are not well understood. Since the prefrontal cortex plays an important role in executive function and the categorization of auditory objects, we hypothesized that neural activity in the prefrontal cortex (PFC) should predict an animal's behavioral reports (decisions) during a category task. To test this hypothesis, we tested PFC activity that was recorded while monkeys categorized human spoken words (Russ et al., 2008b). We found that activity in the ventrolateral PFC, on average, correlated best with the monkeys' choices than with the auditory stimuli. This finding demonstrates a direct link between PFC activity and behavioral choices during a non-spatial auditory task.